Factors affecting women's decision to engage in weaving in Antique. - Maluenda, Charish Ann Juaman
Weaving is a traditional activity in the Philippines that started during the pre-colonial times. It does not only showcase the creativity and ingenuity of Filipinos, it is also an important income generating activity to many communities. The province of Antique is well-known for its weaving industry. Weaving is particularly important to women who are known to dominate the activity. It is considered as one of developmental projects which can alleviate poverty and empower women through income generation., This study was conducted to determine the factors affecting the decision of women to engage in weaving in Antique. A complete enumeration was done among the one hundred thirty-nine members of Sto. Rosario Multipurpose cooperative and Bagtason Loom Weavers Association. Logistic regression model was used to analyze the factors affecting decision of respondents to engage in weaving. The results of the study show that majority of the women who are into weaving are of working age, married and high school graduates. Their most common reason for participating in weaving activity is to generate income for household needs. It was further found out that younger respondents coming from lower income households tend to have higher probability of taking on weaving as an income generating activity. The study also shows that weaving augment household income but increase women's workload. The study concludes that although weaving addresses women's practical need by providing them employment, it also worsens their multiple burdened situation. It is recommended that their practical need be answered by by giving them more livelihood opportunities. More importantly, their strategic needs must be addressed as well by creating policies that will remove manifestations of gender bias one of which is multiple burden.